PONDOK PESANTREN TAHFIDZUL QUR'AN DARUL HIJRAH PUTRA DI MARTAPURA - Laksono, Muhammad Tri; Tharziansyah, Muhammad (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
The increase in the number of Islamic boarding schools shows the increasing public interest inchoosing Islamic boarding schools as a place for Islamic education for their children. This is markedby their need for a better quality Islamic education, which is more inclusive, which is relevant to thetimes, and which does not only focus on academic aspects but can also build good character andbehavior in their children so that they can become a good and successful generation. useful forsociety in the future. The concepts and methods used in the design are passive design which placesmore emphasis on the physical design of the building, such as the facade design, the direction thebuilding is facing, the location and size of windows, the building's ventilation system, and the roomlayout. With this method, it is hoped that the Tahfidzul Qur'an Darul Hijrah Putra Islamic BoardingSchool can produce hafidz of the Qur'an who are faithful, pious, have good morals, areknowledgeable, do good deeds, master science and technology, excel, and excel, in accordance withthe vision of the Islamic boarding school itself.